2015
DOI: 10.3109/14767058.2015.1087500
|View full text |Cite
|
Sign up to set email alerts
|

Timing of elective cesarean section and neonatal morbidity: a population-based study

Abstract: Elective cesarean section at ≥ 39 weeks gestation would significantly reduce neonatal complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…In our own studies, the average time of hospitalisation was 5.42 days for those born at 37 weeks of pregnancy, and in those born at 39 weeks of pregnancy, the significantly shorter period of 4.46 days. Hospitalisations of more than five days for newborns were also observed by other authors [12,16,18]. In the studies of Tita et al, 9.1% of newborns from the 37 th week of pregnancy and 3.6% of newborns from the 39 th week of pregnancy required hospitalisation of more than five days [18].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In our own studies, the average time of hospitalisation was 5.42 days for those born at 37 weeks of pregnancy, and in those born at 39 weeks of pregnancy, the significantly shorter period of 4.46 days. Hospitalisations of more than five days for newborns were also observed by other authors [12,16,18]. In the studies of Tita et al, 9.1% of newborns from the 37 th week of pregnancy and 3.6% of newborns from the 39 th week of pregnancy required hospitalisation of more than five days [18].…”
Section: Discussionsupporting
confidence: 53%
“…In the studies of Tita et al, 9.1% of newborns from the 37 th week of pregnancy and 3.6% of newborns from the 39 th week of pregnancy required hospitalisation of more than five days [18]. In the studies of Vidic et al hospitalisations longer than five days were required by as many as 42.3% of those born at week 37 and 42.5% of those born at week 39 [12]. Conversely, Prefumo et al reported hospitalisations of more than five days for 16.2% of those born at week 37 and the significantly smaller figure of 6.9% of those born at 38 weeks of pregnancy [16].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, our mean gestational age for cesarean delivery was 39 weeks, which allows for pulmonary maturation, since the condition of late cesarean delivery, performed at 39 weeks, decreases admissions of newborns due to respiratory complications 17 . Several other studies [15][16][17][18] have shown that the incidence of respiratory dysfunction is inversely proportional to gestational age. However, these researches have concluded their hypotheses, based on retroactive or DISCUSSION subjective data, which may compromise their interpretation.…”
Section: Interpretation Of Videosmentioning
confidence: 99%
“…However, performing this procedure may have short-and long-term implications for the baby. 2 Human milk is the species-specific food for newborns. It is a highly specialized nourishing and functional substance with a dynamic nature.…”
Section: Introductionmentioning
confidence: 99%